2021
DOI: 10.1007/s10489-021-02352-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 prediction using AI analytics for South Korea

Abstract: The severe spread of the COVID-19 pandemic has created a situation of public health emergency and global awareness. In our research, we analyzed the demographical factors affecting the global pandemic spread along with the features that lead to death due to the infection. Modeling results stipulate that the mortality rate increase as the age increase and it is found that most of the death cases belong to the age group 60-80. Cluster-based analysis of age groups is also conducted to analyze the maximum targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The emergency department (ED) is the frontline for delivering emergency services in hospitals [1], and it is also the department with the most clustered patients and the heaviest rescue tasks [2]. The issue of patient congestion in the ED of hospitals in China is becoming increasingly severe, especially in the top three hospitals in Shanghai and other major cities, which has significantly affected the quality of medical services.…”
Section: Introductionmentioning
confidence: 99%
“…The emergency department (ED) is the frontline for delivering emergency services in hospitals [1], and it is also the department with the most clustered patients and the heaviest rescue tasks [2]. The issue of patient congestion in the ED of hospitals in China is becoming increasingly severe, especially in the top three hospitals in Shanghai and other major cities, which has significantly affected the quality of medical services.…”
Section: Introductionmentioning
confidence: 99%
“…The approach offers an automatic triage, testing visiting patients’ risk of SARS-CoV-2 through checking their underlined disease and their current immigration records to foreign countries. Sinha and Rathi reported that Korea uses artificial intelligence to predict if people infected with the virus survive [ 38 ]. The country achieves this by using machine learning with hyperparameters tuning, profound learning models, and an auto encoder-based method for valuing the effect of contrasting factors on the illness range and gauging the possibilities of survival for those in quarantine [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…where, W hh refers to weight at recurrent neuron and W xh refers to weight at the input neuron. Finally, the output of the recurrent neural network is computed as following (5).…”
Section: Recurrent Neural Networkmentioning
confidence: 99%
“…This helped the covid-affected casualties to recover quickly, thereby minimizing the pace of disease progression. Meanwhile, the scientific community also started working towards designing prediction models to analyze the dynamics of corona pandemic and forecast its severity by using Artificial Intelligence (AI) analytics [5,6]. These AIbased models assisted various medical service providers, thereby allowing them to process medicinal demands, better scale-up, and other emergency healthcare delivery tasks.…”
Section: Introductionmentioning
confidence: 99%